HADISUL ISNAINI AS A COMMUNICATIVE LANGUAGE TEACHING (CLT)-BASED MODEL IN 1ST CAMPUS GONTOR PUTRI - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Siti Nikmatul Rochma; Nuraeni Rahmawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study investigates Hadisul Isnaini as a Communicative Language Teaching (CLT)-based model in enhancing Arabic proficiency at Gontor Putri Campus 1. Employing a qualitative case study design, the research explores how this weekly program integrates language correction (iṣlāḥ al-lughah), communicative practice, and habitual reinforcement within a pesantren environment. Data were collected through observations, in-depth interviews, and document analysis. The findings reveal that Hadisul Isnaini effectively improves students' communicative competence and confidence by creating a structured yet immersive language environment. The program also demonstrates a balanced integration of fluency and accuracy, addressing a common limitation in CLT implementation. From a curriculum perspective, this study conceptualizes Hadisul Isnaini as a form of hidden or co-curricular framework that strengthens formal instruction through continuous social interaction and environmental exposure. The study proposes a habitual communicative curriculum model as its main contribution, emphasizing the importance of integrating structured practice, social mediation, and institutional culture in language learning. These findings offer both theoretical and practical implications for developing context-sensitive language programs in similar educational settings.